Utility of fetal facial markers on a second trimester genetic sonogram in screening for Down syndrome in a high-risk Thai population - Savitree Pranpanus; Kanokkarn Keatkongkaew; Manaphat Suksai (BMC, 2022)
Abstract Background To establish the reference ranges and evaluate the efficacy of the fetal facial sonomarkers prenasal thickness (PT), nasal bone length (NBL), PT/NBL ratio and NBL/PT ratio for Down syndrome screening in the second trimester of high-risk pregnancies using two-dimensional (2D) ultrasound. Methods A prospective study was done in Thai pregnant women at high risk for structural and chromosomal abnormalities between May 2018 and May 2019. The main exclusion criteria were any fetal anatomical anomaly detected on ultrasonography or postpartum examination, abnormal chromosome or syndrome other than Down syndrome. Ultrasounds were performed in 375 pregnant women at 14 to 22 weeks' gestation and the fetal facial parameters were analyzed. Down syndrome results were confirmed by karyotyping. The reference ranges of these facial ultrasound markers were constructed based on the data of our population. The Down syndrome screening performance using these facial ultrasound markers was evaluated. Results In total, 340 euploid fetuses and 11 fetuses with Down syndrome met the inclusion criteria. The PT, NBL, and PT/NBL ratios in the euploid fetuses gradually increased with gestation progression while the NBL/PT ratio gradually decreased between 14-22 weeks' gestation. The NBL, PT/NBL ratio, and NBL/PT ratio all had 100% sensitivity and PT had 91% sensitivity. These facial markers had 100% negative predictive value for Down syndrome screening in the second trimester. The Bland-Altman analysis showed the intra- and inter-observer variations of PT and NBL had high intraclass correlation coefficients (ICC) in both operators, with ICCs of 0.98 and 0.99 and inter-observer ICCs of 0.99 for both operators. Conclusion The facial ultrasound markers are very useful for second trimester Down syndrome screening in our population. These facial ultrasound markers were easily identifiable and highly consistent either intra- or inter-operator by using widely-available 2D ultrasound. However, the reference ranges for these markers need to be constructed based on individual populations. Trial registration Registration number: REC 61-029-12-3. Date of registration: 18 May 2018.